Landscape change and the sustainable development strategy of different types of ethnic villages driven by the grain for Green Program - Wang, Dan; Higgitt, David; Tang, Yu-Ting; He, Jun; Guo, Luo (MDPI, 2018)
The Grain for Green Program (GGP) is an important ecological project in China that was implemented to tackle serious soil erosion and forest loss for sustainable development. Investigating landscape change is an efficient way to monitor and assess the implementation of GGP. In this paper, 180 ethnic villages, including 36 Miao and Dong (MD) villages with combined populations of Miao people and Dong people, 65 Dong villages, and 79 Miao villages in Qiandongnan Prefecture were selected to investigate the influence of GGP on ethnic villages by evaluating the landscape changes before and after the implementation of the GGP within 1-km and 2-km distance buffers around ethnic villages. The results show that the GGP has more significant positive impacts on reforestation around Miao villages than Dong villages and MD villages because Miao villages are mostly located in higher and steeper areas, which are the focus of the GGP. Based on the analysis, a continuation of the GGP in Qiandongnan Prefecture is recommended, as it can incentivize the recovery of forest cover in steeper slopes. More attention should now be paid to the Dong villages and MD villages, which were not previously a focus of the GGP.